1981
DOI: 10.1172/jci110216
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-releasing Hormone Stimulation of Prolactin Release from Clonal Rat Pituitary Cells

Abstract: A B S T R A C T Thyrotropin-releasing hormone (TRH)stimulates prolactin release and 45Ca2+ efflux from GH3 cells, a clonal strain of rat pituitary cells. Elevation of extracellular K+ also induces prolactin release and increases 45Ca2+ efflux from these cells. In this report, we distinguish between TRH and high K+ as secretagogues and show that TRH-induced release of prolactin and 45Ca2+ is independent of the extracellular Ca21 concentration, but the effect of high K+ on prolactin release and 45Ca2+ efflux is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Stimulated phosphorylation is detected at 15 sec, a time scale consistent with the organelle Ca2+ efflux described here. Although our data do not exclude the possibility that TRH may stimulate influx of extracellular Ca2+, the observation that calcium channel blockers fail to inhibit TRH-induced Ca2+ pool depletion is consistent with other studies that indicated a nonobligatory role for Ca2+ influx in TRH stimulation of Ca2" efflux and hormone secretion (3)(4)(5) …”
supporting
confidence: 86%
See 3 more Smart Citations
“…Stimulated phosphorylation is detected at 15 sec, a time scale consistent with the organelle Ca2+ efflux described here. Although our data do not exclude the possibility that TRH may stimulate influx of extracellular Ca2+, the observation that calcium channel blockers fail to inhibit TRH-induced Ca2+ pool depletion is consistent with other studies that indicated a nonobligatory role for Ca2+ influx in TRH stimulation of Ca2" efflux and hormone secretion (3)(4)(5) …”
supporting
confidence: 86%
“…In GH3 cells, a clonal TRH-responsive rat pituitary tumor cell line, TRH-induced 45Ca2+ efflux was shown to be independent of extracellular Ca21 (3,5). In addition, it has been found that stimulation of prolactin release by TRH may not require extracellular Ca2+ (2)(3)(4)(5) Digitonin Permeabilization of Cells. Cells incubated as above (4Ca2+ steady-state or 45Ca2+ uptake experiments) were centrifuged at 4°C (800 x g, 3 min) and washed once with icecold Na+-, Ca2+-free HBSS (formulated with choline chloride instead of NaCl).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it must be pointed out that mobilization of intracellular Ca +2 as a mechanism of secretagogue action is not without precedent, as it has been recently shown to mediate TRH-induced PRL release from normal pituitary cells and clonal pituitary cell lines (40)(41)(42). Examination of the mechanism by which PGE 2 may mobilize intraterminal Ca +2 in the ME warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%